Preparation method of high-purity sodium pyruvate with anti-browning

CN122916833APending Publication Date: 2026-10-16SINOPHARM CHEM REAGENT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611143392.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]本发明的目的在于提供一种抗褐变高纯度丙酮酸钠的制备方法,旨在解决丙酮酸钠在制备和储存过程中容易因金属离子和氯离子残留催化氧化而发生褐变发黄的问题

Benefits of technology

本发明提供的这种抗褐变高纯度丙酮酸钠的制备方法,具有如下的优异效果:①从根本上抑制褐变发黄:通过螯合树脂色谱深度去除催化氧化反应的铁、铜等重金属离子(含量≤1ppm),通过强碱性阴离子交换树脂色谱深度去除促进褐变的氯离子(含量≤10ppm),从源头上消除了导致丙酮酸钠褐变发黄的关键催化因素,所得产品为纯白色结晶粉末(白度值L≥98),在制备过程中不发生褐变,在40℃、75%相对湿度的加速稳定性试验中放置6个月后产品白度值仍L≥97,而传统方法制备的产品在相同条件下1~2个月即出现明显发黄,6个月后白度值降至80~85;②产品纯度高:本发明通过离子交换-色谱耦合纯化结合反溶剂结晶制得的产品的纯度≥99.8%,干燥失重≤0.3%;③氯化物含量极低:本发明方法制备的产品中氯化物含量≤10.0ppm,远低于现行药典标准(≤100ppm);④重金属含量极低:本发明方法制备的产品中重金属含量≤1.0ppm,达到超纯级标准;⑤热稳定性优异:由于重金属离子和氯离子被深度去除,产品在50~80℃减压干燥过程中不会发生热致褐变,干燥后产品白度值(L)≥98,而传统方法制备的产品干燥后白度值通常为92~96;⑥工艺绿色环保:本发明方法采用的离子交换树脂可多次再生循环使用(20次以上仍保持去除率>97%),而且反溶剂可回收循环使用,减少了有机溶剂消耗和废液排放,在降低生产成本的同时工艺也更为环保。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_12
    Figure SMS_12
  • Figure SMS_17
    Figure SMS_17
  • Figure SMS_19
    Figure SMS_19
Patent Text Reader

Abstract

The application discloses a preparation method of high-purity anti-browning sodium pyruvate, S1, pyruvic acid is dissolved in water, and a basic sodium source is added for neutralization reaction to obtain a sodium pyruvate neutralization solution; S2, activated carbon is added to the sodium pyruvate neutralization solution for decolorization, and filtration is performed to obtain a pre-decolorization solution; S3, the pre-decolorization solution is passed through a first chromatographic column filled with chelating resin again, and the chelating resin is selected from iminodiacetic acid type chelating resin or amino phosphonic acid type chelating resin; S4, effluent of the step S3 is passed through a second chromatographic column filled with strong basic anion exchange resin, the functional group of the strong basic anion exchange resin is quaternary ammonium group, and the strong basic anion exchange resin is used for selective adsorption of chloride ions in the effluent; S5, the effluent of the step S4 is concentrated under reduced pressure, a counter solvent is added for crystallization to obtain a crystallization mixture; S6, the crystallization mixture is separated, and the solid is washed with a washing solution to obtain sodium pyruvate wet products; and S7, the sodium pyruvate wet products are dried under reduced pressure to obtain high-purity sodium pyruvate finished products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-purity reagent preparation technology, and more specifically, to a method for preparing high-purity sodium pyruvate with anti-browning properties. Background Technology

[0002] Sodium pyruvate (chemical formula C3H3NaO3, molecular weight 110.04) is a water-soluble white crystalline powder and a naturally occurring endogenous small molecule compound in human metabolism. Sodium pyruvate has the function of scavenging reactive oxygen free radicals and maintaining NAD5 levels. + The role of the NADH ratio is widely used in the pharmaceutical field as a buffer, excipient, and antioxidant; in the biological field as a core additive for cell culture media; and in the food field as a preservative and acidulant.

[0003] Sodium pyruvate is prone to browning and yellowing during preparation and storage, severely affecting product quality and application effectiveness. Studies have shown that the browning and yellowing of sodium pyruvate falls under the category of non-enzymatic browning, primarily caused by the following factors: ① Catalytic oxidation by metal ions: iron ions (Fe³⁺) + / Fe² + ), copper ions (Cu²⁺) + Transition metal ions such as iron and copper are strong catalysts for the oxidative degradation of sodium pyruvate. In the field of food chemistry, it is widely recognized that metal ions such as iron and copper can significantly accelerate the Maillard reaction and ascorbic acid oxidative browning. Their catalytic mechanism lies in the fact that metal ions promote the enolization and oxidative dehydrogenation of carbonyl compounds through single-electron transfer, generating colored quinone polymers. Even trace amounts of metal ions (ppm level) can significantly accelerate the browning process. In traditional preparation processes, iron and copper ions are inevitably introduced into the raw material pyruvate, neutralizing alkali, and process water, and conventional activated carbon decolorization and ethanol crystallization cannot effectively remove them. ② The indirect browning-promoting effect of chloride ions: Although chloride ions themselves do not directly cause browning, their presence can form chloride complexes with metal ions, altering the coordination ring of the metal ions. The oxidation-reduction potential of sodium pyruvate is enhanced by the presence of metal ions, which in turn enhance the catalytic oxidation activity of sodium pyruvate. In addition, under acidic conditions, residual chloride ions may form trace amounts of oxidizing species such as hypochlorous acid, accelerating the oxidation and discoloration of sodium pyruvate. ③ Thermal browning during drying: If sodium pyruvate contains impurities (especially metal ions and chloride ions) during the heating and drying process, Maillard reaction and caramelization reaction will occur at 50-80℃, resulting in a darker product color (the higher the impurity content, the more severe the thermal browning). ④ Slow browning during storage: Even if the color is qualified when leaving the factory, if the content of residual metal ions and chloride ions in the product is high, they will continue to catalyze the oxidation and degradation of sodium pyruvate during long-term storage (especially under high temperature and high humidity conditions), causing the product to gradually turn yellow.

[0004] However, existing methods for preparing and purifying sodium pyruvate have the following shortcomings: ① Chemical synthesis-ethanol crystallization method: Pyruvate is used as a raw material, neutralized with sodium hydroxide, and then ethanol is added for crystallization. Although this method is simple, the purity of the product is limited by the purity of the raw material. During the crystallization process, metal ions and chloride ions are easily introduced as impurities. The heavy metal content in the product can usually reach 5-20 ppm, and the chloride content can reach 50-200 ppm. These residual impurities will continue to catalyze oxidation reactions during subsequent drying and storage, causing the product to turn slightly yellow during preparation and to show obvious browning after 3-6 months of storage; ② Activated carbon Decolorization-recrystallization method: Although this method can improve product purity through activated carbon decolorization and ethanol recrystallization, activated carbon has limited ability to remove soluble ionic impurities. The removal rate of metal ions and chloride ions is usually less than 30%, which cannot fundamentally solve the browning problem; ③ Enzyme conversion-membrane separation method: This method uses lactate oxidase to catalyze lactic acid to produce sodium pyruvate, which is then filtered through a ceramic membrane, decolorized with activated carbon, concentrated by vacuum distillation, spray-dried, and extracted with organic solvents. This method is mild, but the removal rate of monovalent ions is limited, and the chloride and metal ion content in the product is still relatively high. The product is prone to thermal browning under the high temperature conditions of spray drying.

[0005] In summary, the fundamental problem with existing methods for preparing sodium pyruvate is the lack of efficient and selective removal of key impurities (metal ions and chloride ions) that cause browning, thus failing to inhibit the browning and yellowing of sodium pyruvate at its source. Summary of the Invention

[0006] The purpose of this invention is to provide a method for preparing high-purity sodium pyruvate with anti-browning properties, which aims to solve the problem that sodium pyruvate is prone to browning and yellowing during preparation and storage due to residual metal ions and chloride ions catalytic oxidation.

[0007] To achieve the above objectives, the present invention is implemented through the following technical solution: This invention provides a method for preparing high-purity sodium pyruvate with anti-browning properties, the method comprising the following steps: S1, Neutralization reaction: Pyruvic acid is dissolved in water, and then an alkaline sodium source is added to carry out a neutralization reaction to obtain sodium pyruvate neutralized solution; S2. Pre-decolorization treatment: Add activated carbon to the sodium pyruvate neutralization solution, stir and decolorize, then filter to obtain a pre-decolorized solution; S3, Heavy metal ion adsorption: The pre-decolorized solution is passed through a first chromatographic column packed with chelating resin, wherein the chelating resin is selected as an iminodiacetic acid type chelating resin or an aminophosphonic acid type chelating resin. S4. Chloride ion removal: The effluent from step S3 is passed through a second chromatographic column packed with a strong basic anion exchange resin. The functional group of the strong basic anion exchange resin is a quaternary ammonium group, which is used to selectively adsorb chloride ions in the effluent. S5. Concentration and crystallization: The effluent from step S4 is concentrated under reduced pressure, and then an antisolvent is added to crystallize, resulting in a crystalline mixture. S6. Solid-liquid separation and washing: The crystallized mixture is separated into solid and liquid phases. The obtained solid is washed with a washing solution to obtain wet sodium pyruvate. S7. Drying: The wet sodium pyruvate is dried under reduced pressure to obtain high-purity sodium pyruvate product.

[0008] The method for preparing anti-browning high-purity sodium pyruvate provided by this invention is a method for preparing anti-browning high-purity sodium pyruvate based on ion exchange-chromatographic coupling purification. It inhibits the browning reaction from the source by deeply removing key impurities that cause browning.

[0009] In this invention, the chelating resin (iminodiacetic acid type chelating resin) forms stable five-membered ring chelates with heavy metal ions through functional groups. Its selectivity for divalent heavy metal ions is far higher than that for monovalent sodium ions, with a selectivity ratio of approximately 5000:1. Even under high-concentration sodium salt conditions, it can efficiently capture trace heavy metal ions, which is impossible with ordinary cation exchange resins. Meanwhile, the strongly basic anion exchange resin undergoes an exchange reaction with chloride ions through quaternary ammonium groups, maintaining a fully ionized state within a pH range of 6.5–7.5, exhibiting high selectivity and high exchange capacity for chloride ions. This application couples chelating resin chromatography with anion exchange resin chromatography for the deep purification of sodium pyruvate, removing key impurities that cause browning at the source and effectively inhibiting the browning reaction.

[0010] Furthermore, a method for preparing high-purity sodium pyruvate with anti-browning properties: Step S1, neutralization reaction: Pyruvate is dissolved in purified water, and then an alkaline sodium source is added under stirring to carry out a neutralization reaction. The reaction temperature is controlled to not exceed 40°C, and the pH of the reaction solution is adjusted to 6.5-7.5 to obtain a neutralized sodium pyruvate solution. The alkaline sodium source is selected from one or more of sodium hydroxide, sodium carbonate, and sodium bicarbonate, and the molar ratio of pyruvic acid to alkaline sodium source is 1:(0.95~1.05).

[0011] Furthermore, a method for preparing high-purity sodium pyruvate with anti-browning properties: Step S2, pre-decolorization treatment: Add activated carbon to the sodium pyruvate neutralization solution and stir and decolorize at 40-60°C for 20-60 minutes, then filter to remove the activated carbon to obtain the pre-decolorized solution.

[0012] Furthermore, a method for preparing high-purity sodium pyruvate with anti-browning properties: in step S3, the flow rate of the pre-decolorized solution passing through the first chromatographic column is set to 2.0–5.0 BV / h; the particle size of the chelating resin is 0.3–1.2 mm, the height-to-diameter ratio of the first chromatographic column is (8–15):1, and the operating temperature is 20–30 °C.

[0013] Furthermore, a method for preparing high-purity sodium pyruvate with anti-browning properties: in step S4, the flow rate of the effluent passing through the second chromatographic column is set to 2.0–5.0 BV / h; the particle size of the strongly basic anion exchange resin is 0.3–1.2 mm, the height-to-diameter ratio of the second chromatographic column is (8–15):1, and the operating temperature is 20–30 °C.

[0014] Furthermore, a method for preparing high-purity sodium pyruvate with anti-browning properties: the first chromatographic column in step S3 and the second chromatographic column in step S4 are pretreated before use; The pretreatment process for the first chromatographic column is as follows: First, the column is regenerated by passing a 0.5–2.0 mol / L hydrochloric acid solution through it at a flow rate of 2.0–5.0 BV / h. Then, it is washed with purified water until neutral. Next, it is converted to the sodium form using a 0.5–2.0 mol / L sodium hydroxide solution, and finally washed with purified water until neutral. The pretreatment process for the second chromatographic column is as follows: First, the column is regenerated by passing a 0.5–2.0 mol / L sodium hydroxide solution through it at a flow rate of 2.0–5.0 BV / h. Then, it is washed with purified water until neutral, converting it to the OH form. - type.

[0015] Furthermore, a method for preparing high-purity sodium pyruvate with anti-browning properties: Step S5, concentration and crystallization: The effluent is concentrated under reduced pressure in a water bath at 55-65°C and 0.05-0.1 MPa until the concentration of sodium pyruvate is 500-700 g / L, and then an antisolvent is added dropwise and crystallized at 0-10°C for 2-6 hours to obtain a crystalline mixture; wherein, the antisolvent is anhydrous ethanol or isopropanol, the volume ratio of the added antisolvent to the volume of the concentrated solution is (2-6):1, and the dropwise addition rate of the antisolvent is 1-5 ml / min.

[0016] Furthermore, a method for preparing high-purity sodium pyruvate with anti-browning properties is provided: In step S6, the washing solution is anhydrous ethanol or an aqueous ethanol solution with a volume fraction of 90-95%, and the washing is performed 1-3 times; in step S7, the vacuum degree of the reduced-pressure drying is 0.08-0.1 MPa, the drying temperature is 50-80℃, and the drying time is 4-12 hours. After drying in step S7, high-purity sodium pyruvate is obtained. The finished product does not undergo browning or yellowing during the preparation process, and its whiteness value L is [value missing] after 6 months in an accelerated stability test at 40℃ and 75% relative humidity. ≥97.

[0017] Furthermore, a method for preparing high-purity sodium pyruvate with anti-browning properties includes step S8, resin regeneration: After use, the chelating resin column of step S3 is regenerated by passing it through a 0.5–2.0 mol / L hydrochloric acid solution at a flow rate of 2.0–5.0 BV / h. The regenerated solution is collected for heavy metal recovery, and the regenerated chelating resin is recycled after being converted to the sodium form. After use, the anion exchange resin column of step S4 is regenerated by passing it through a 0.5–2.0 mol / L sodium hydroxide solution at a flow rate of 2.0–5.0 BV / h. The regenerated anion exchange resin is converted to the OH form. - It can be reused after being shaped.

[0018] Furthermore, a method for preparing high-purity sodium pyruvate with anti-browning properties involves reversing the order of steps S3 and S4, i.e., first performing anion exchange chromatography to remove chloride ions, and then performing chelating resin chromatography to remove heavy metal ions.

[0019] The beneficial effects of this invention are: The method for preparing high-purity sodium pyruvate with anti-browning properties provided by this invention has the following excellent effects: ① It fundamentally inhibits browning and yellowing: Heavy metal ions such as iron and copper (content ≤1ppm) that catalyze oxidation reactions are removed through chelating resin chromatography, and chloride ions (content ≤10ppm) that promote browning are removed through strong basic anion exchange resin chromatography. This eliminates the key catalytic factors that cause sodium pyruvate to brown and yellow at the source, resulting in a pure white crystalline powder (whiteness value L). ≥98), no browning occurs during preparation, and the product's whiteness value remains L after 6 months in an accelerated stability test at 40℃ and 75% relative humidity. ≥97, while products prepared by traditional methods show obvious yellowing within 1-2 months under the same conditions, and the whiteness value drops to 80-85 after 6 months; ② High product purity: The purity of the product obtained by the present invention through ion exchange-chromatographic coupling purification combined with anti-solvent crystallization is ≥99.8%, and the drying loss is ≤0.3%; ③ Extremely low chloride content: The chloride content in the product prepared by the method of the present invention is ≤10.0ppm, far lower than the current pharmacopoeia standard (≤100ppm); ④ Extremely low heavy metal content: The heavy metal content in the product prepared by the method of the present invention is ≤1.0ppm, reaching the ultrapure grade standard; ⑤ Excellent thermal stability: Due to the deep removal of heavy metal ions and chloride ions, the product will not undergo heat-induced browning during vacuum drying at 50-80℃, and the whiteness value of the product after drying (L) remains high. The whiteness of the product prepared by the traditional method is ≥98, while the whiteness value of the product after drying is usually 92-96; ⑥ The process is green and environmentally friendly: the ion exchange resin used in the method of this invention can be regenerated and recycled multiple times (still maintaining a removal rate of >97% after more than 20 times), and the antisolvent can be recycled, reducing the consumption of organic solvents and waste liquid discharge. While reducing production costs, the process is also more environmentally friendly. Detailed Implementation

[0020] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the present invention or its application or use. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0021] Example 1

[0022] Example 1 provides a method for preparing high-purity sodium pyruvate with anti-browning properties, which includes the following specific steps: S1. Neutralization reaction: Add 100g of pyruvate (99.5% purity) and 200ml of purified water to a 500ml three-necked flask, and turn on the stirrer (200rpm). Then weigh 45.4g of sodium hydroxide (99.0% purity) to prepare a 30% sodium hydroxide aqueous solution. Under ice bath cooling conditions, slowly add the sodium hydroxide aqueous solution dropwise to the pyruvate aqueous solution, controlling the dropping rate so that the reaction temperature does not exceed 30℃. After the addition is complete, continue stirring for 30 minutes, and adjust the pH of the reaction solution to 7.1 to obtain the sodium pyruvate neutralized solution. S2. Pre-decolorization treatment: Add 3.0g of activated carbon to the sodium pyruvate neutralization solution above and heat to 50℃ for stirring and decolorization for 40 minutes. Then filter while hot to remove the activated carbon and obtain the pre-decolorized solution. S3. Heavy metal ion adsorption: The pre-decolorized solution is passed through a first chromatographic column filled with chelating resin (the first chromatographic column has an inner diameter of 30 mm, a height of 300 mm, a height-to-diameter ratio of 10:1, and a resin packing volume of 200 ml) at a flow rate of 3.0 BV / h. The temperature of the first chromatographic column is 25℃. The chelating resin is an iminodiacetic acid type chelating resin (resin type D401, particle size 0.4-0.8 mm), and its functional group is an iminodiacetic acid group. It is used to selectively chelate and adsorb trace heavy metal ions in the pre-decolorized solution in the presence of a large amount of sodium ions. The selectivity coefficient of the chelating resin for divalent heavy metal ions is more than 5000 times that for monovalent sodium ions, thereby eliminating the catalytic effect of heavy metal ions on the oxidative browning of sodium pyruvate from the source. S4. Chloride ion removal: The effluent from step S3 is adjusted to pH 7.0 with pyruvate, and then passed at a flow rate of 3.0 BV / h through a second chromatographic column (201×7 resin, particle size 0.4-0.8 mm, inner diameter 30 mm, column height 300 mm, height-to-diameter ratio 10:1, resin packing volume 200 ml) filled with strong basic anion exchange resin (resin type 201×7, particle size 0.4-0.8 mm). The temperature of the second chromatographic column is 25℃. The functional group of the strong basic anion exchange resin is quaternary ammonium group, which is used to selectively adsorb chloride ions in the effluent and eliminate the indirect promoting effect of chloride ions on the browning reaction. S5. Concentration and Crystallization: The effluent from step S4 is transferred to a rotary evaporator and concentrated under reduced pressure in a 60°C water bath and a vacuum of 0.08MPa until the sodium pyruvate concentration in the concentrate is approximately 600 g / L. The concentrate is then transferred to a crystallization vessel and cooled to 5°C. Anhydrous ethanol is added to the concentrate at a dropping rate of 3.0 ml / min under stirring (150 rpm), with the total ethanol volume to the concentrate volume ratio being 4:1. After the addition is complete, the mixture is stirred and crystallized at 5°C for 4 hours to obtain a white crystalline mixture. S6. Solid-liquid separation and washing: The solid-liquid mixture of crystals is separated by vacuum filtration. The obtained solid is washed twice with anhydrous ethanol and then dried to obtain wet sodium pyruvate. S7. Drying: Transfer the wet sodium pyruvate to a vacuum drying oven and dry it for 8 hours at 60°C and a vacuum of 0.08 MPa to obtain high-purity sodium pyruvate product.

[0023] Specifically, the first chromatographic column in step S3 and the second chromatographic column in step S4 of the above embodiment 1 were pretreated before use; The pretreatment process of the first chromatographic column is as follows: first, the first chromatographic column is regenerated by passing a 1.0 mol / L hydrochloric acid solution through it at a flow rate of 3.0 BV / h, then washed with purified water until neutral, then converted to sodium form with a 1.0 mol / L sodium hydroxide solution, and finally washed with purified water until neutral, and the eluent is collected. The pretreatment process for the second chromatographic column is as follows: First, the column is regenerated by passing a 1.0 mol / L sodium hydroxide solution through it at a flow rate of 3.0 BV / h, followed by washing with purified water until neutral, thus converting it to OH-. - Type, for collecting outflowing liquid.

[0024] In the method of the above embodiment 1: the first chromatographic column and the second chromatographic column in steps S3 and S4 are arranged in series, and the first chromatographic column is located upstream of the second chromatographic column, so that the pre-decolorized liquid is successively removed by heavy metal ions and chloride ions. The operating flow rates of the first chromatographic column and the second chromatographic column are the same, so that the system can run continuously under steady state. The chloride content in the effluent is ≤10.0ppm and the heavy metal content is ≤1.0ppm.

[0025] Product testing: The product obtained in Example 1 was tested, and the results are as follows: ① Appearance: Pure white crystalline powder, without any yellowing; ② Purity (HPLC method): 99.8%; ③ Loss on drying: 0.2%; ④ pH value (5% aqueous solution): 6.9; ⑤ Chloride content (as Cl... - ⑥ Heavy metal content (as Pb): 0.5 ppm; ⑦ Iron ion content: 0.3 ppm; ⑧ Copper ion content: <0.1 ppm; ⑨ Whiteness value (L ): 98.5; ⑩ Crystallization yield: 93.5% (based on pyruvate feed amount).

[0026] Example 2

[0027] Example 2 provides a method for preparing high-purity sodium pyruvate with anti-browning properties, which includes the following specific steps: S1. Neutralization reaction: Add 100g of pyruvate (99.5% purity) and 200ml of purified water to a 500ml three-necked flask, and start stirring (200rpm). Then weigh 45.4g of sodium hydroxide (99.0% purity) to prepare a 30% sodium hydroxide aqueous solution. Under ice bath cooling conditions, slowly add the sodium hydroxide aqueous solution dropwise to the pyruvate aqueous solution, controlling the dropping rate so that the reaction temperature does not exceed 40℃. After the addition is complete, continue stirring for 30 minutes, and adjust the pH of the reaction solution to 6.5 to obtain the sodium pyruvate neutralized solution. S2. Pre-decolorization treatment: Add 3.0g of activated carbon to the sodium pyruvate neutralization solution above and heat to 45℃ for stirring and decolorization for 20 minutes. Then filter while hot to remove the activated carbon and obtain the pre-decolorized solution. S3. Heavy metal ion adsorption: The pre-decolorized solution is passed through a first chromatographic column filled with chelating resin (the height-to-diameter ratio of the first chromatographic column is 8:1) at a flow rate of 5.0 BV / h. The temperature of the first chromatographic column is 30℃. The chelating resin is an aminophosphonic acid type chelating resin (resin type D403, particle size 0.4~0.8mm). S4. Chloride ion removal: The effluent from step S3 is passed through a second chromatographic column (height-to-diameter ratio of the second chromatographic column is 8:1) packed with a strong basic anion exchange resin at a flow rate of 5.0 BV / h, and the temperature of the second chromatographic column is 30℃. S5. Concentration and Crystallization: The effluent from step S4 is transferred to a rotary evaporator and concentrated under reduced pressure in a 55°C water bath and a vacuum of 0.05MPa until the sodium pyruvate concentration in the concentrate is approximately 500g / L. The concentrate is then transferred to a crystallization vessel and cooled to 2°C. Anhydrous ethanol is added to the concentrate at a dropping rate of 1.0ml / min under stirring (150rpm), with the total ethanol volume to the concentrate volume ratio being 2:1. After the addition is complete, the mixture is stirred and crystallized at 2°C for 2 hours to obtain a white crystalline mixture. S6. Solid-liquid separation and washing: The solid-liquid mixture of crystals is separated by vacuum filtration. The obtained solid is washed three times with an ethanol aqueous solution of 95% by volume. After washing, it is dried to obtain wet sodium pyruvate. S7. Drying: Transfer the wet sodium pyruvate to a vacuum drying oven and dry it at 55°C and 0.1 MPa for 5 hours to obtain high-purity sodium pyruvate product.

[0028] In Example 2, the first and second chromatographic columns were pretreated before use. The pretreatment process for the first column was as follows: it was regenerated by passing a 0.5 mol / L hydrochloric acid solution through it at a flow rate of 2.0 BV / h, then washed with purified water until neutral, then converted to the sodium form using a 0.5 mol / L sodium hydroxide solution, and finally washed with purified water until neutral, and the eluent was collected. The pretreatment process for the second column was as follows: it was regenerated by passing a 0.5 mol / L sodium hydroxide solution through it at a flow rate of 2.0 BV / h, then washed with purified water until neutral, converting to the OH form. - Type, for collecting outflowing liquid.

[0029] Product testing: The product obtained in Example 2 was tested, and the results are as follows: ① Appearance: Pure white crystalline powder, without any yellowing; ② Purity: 99.8%; ③ Loss on drying: 0.2%; ④ pH value (5% aqueous solution): 6.9; ⑤ Chloride content (as Cl... - ⑥ Heavy metal content (as Pb): 0.7 ppm; ⑦ Iron ion content: 0.5 ppm; ⑧ Copper ion content: <0.1 ppm; ⑨ Whiteness value (L ): 98.2; ⑩ Crystallization yield: 93.2%. The aminophosphonic acid chelating resin used in Example 2 has slightly lower selectivity for heavy metal ions than the iminodiacetic acid type, but it has stronger acid resistance and is suitable for applications with lower pH values.

[0030] Example 3

[0031] The difference between Example 3 and Example 1 is that the order of steps S3 and S4 is reversed in Example 3. That is, in Example 3, anion exchange chromatography is performed first to remove chlorine, and then chelation resin chromatography is performed to remove heavy metals. The remaining process conditions are the same as in Example 1.

[0032] Product testing: The product obtained in Example 3 was tested, and the results are as follows: ① Appearance: Pure white crystalline powder, without any yellowing; ② Purity: 99.7%; ③ Loss on drying: 0.2%; ④ pH value (5% aqueous solution): 6.9; ⑤ Chloride content (as Cl... - ⑥ Heavy metal content (as Pb): 0.6 ppm; ⑦ Iron ion content: 0.3 ppm; ⑧ Copper ion content: <0.1 ppm; ⑨ Whiteness value (L ): 98.3; ⑩ Crystallization yield: 93.0%. Whiteness value (L) after 6 months of accelerated stability testing. The value was 96.8. Both process sequences in Examples 1 and 3 achieved excellent purification results, but the sequence of removing heavy metals first and then removing chlorine was better in terms of resin lifespan.

[0033] Comparative Example 1

[0034] Comparative Example 1 uses the traditional ethanol crystallization method: Pyruvic acid is dissolved in water, neutralized to pH 7.0 with sodium hydroxide, decolorized with activated carbon, and then 4 times the volume of ethanol is added directly to precipitate crystals. After filtration and drying, the product is obtained.

[0035] The test results of the product obtained in Comparative Example 1 were as follows: ① Appearance: The product was slightly yellow; ② Purity: 98.5%; ③ Chloride content: 85.0 ppm; ④ Heavy metal content: 12.0 ppm; ⑤ Iron ion content: 5.2 ppm; ⑥ Whiteness value (L ): 94.2.

[0036] The product obtained in Comparative Example 1 showed a significant darkening in color after being stored at 40°C and 75% relative humidity for 30 days, with the whiteness value dropping to 90.5. After 6 months, it further decreased to 80.5.

[0037] Comparative Example 2

[0038] The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 omits step S3 (chelating resin chromatography to remove heavy metals) and only performs step S4 (anion exchange chromatography to remove chlorine), while the remaining process conditions are the same as in Example 1.

[0039] Product test results of Comparative Example 2: ① Appearance: The product is slightly yellow; ② Purity: 98.3%; ③ Chloride content: 8.0 ppm; ④ Heavy metal content: 10.0 ppm; ⑤ Iron ion content: 4.8 ppm; ⑥ Whiteness value (L ): 95.8.

[0040] The whiteness value of the product obtained in Comparative Example 2 decreased to 92.1 after 30 days of storage at 40℃ and 75% relative humidity, to 88.6 after 60 days, and to 82.3 after 6 months.

[0041] The results showed that Comparative Example 2 only removed chloride ions but not heavy metal ions. The residual iron ions and other heavy metals in the product would still catalyze the oxidation reaction, leading to browning and yellowing.

[0042] Comparative Example 3

[0043] The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 omits step S4 (anion exchange chromatography to remove chlorine) and only performs step S3 (chelate resin chromatography to remove heavy metals), while the remaining process conditions are the same as in Example 1.

[0044] Product testing results of Comparative Example 3: ① Appearance: White; ② Purity: 99.2%; ③ Chloride content: 78.0 ppm; ④ Heavy metal content: 0.6 ppm; ⑤ Iron ion content: 0.2 ppm; ⑥ Whiteness value (L ): 97.5.

[0045] The whiteness value of the product in Comparative Example 3 decreased to 96.0 after 30 days of storage at 40℃ and 75% relative humidity, to 94.5 after 60 days, and to 91.2 after 6 months.

[0046] The results showed that Comparative Example 3 removed only heavy metals without removing chloride ions, and the product had a good color in the initial stage, but the presence of chloride ions would still promote browning reaction during long-term storage.

[0047] Accelerated stability testing: The sodium pyruvate products obtained in Example 1 and Comparative Example 1 were simultaneously placed in a constant temperature and humidity chamber at 40°C and 75% relative humidity for accelerated stability testing. Color changes were observed periodically and whiteness values ​​were measured. The results are shown in Table 1. Table 1 shows the color changes during accelerated stability testing.

[0048] Note: Whiteness value (L) The higher the value, the whiter and brighter the sample.

[0049] The results in Table 1 show that the sodium pyruvate prepared by the method of the present invention remained off-white (L) after 6 months in the accelerated stability test. =97.0), while the product of Comparative Example 1 turned light yellow after 1 month and dark yellow after 3 months. This fully demonstrates that the anti-browning ability of sodium pyruvate is significantly improved after deep removal of metal ions and chloride ions through the coupling purification of chelating resin and anion exchange resin.

[0050] The whiteness value in this invention is measured under the following specific conditions: ① Instrument: Konica Minolta CM-5 spectrophotometer; ② Light source: D65 standard light source; ③ Observation angle: 10°; ④ Measuring aperture: 8.0mm; ⑤ Measurement mode: SCI (including specular reflection); ⑥ Sample preparation: Sodium pyruvate powder was placed into a quartz powder test box and compacted until the surface was flat. Each sample was measured at 3 different locations, and the average value was taken.

[0051] For sodium pyruvate, a white crystalline powder, whiteness value is the core indicator for evaluating its color quality and whiteness. The whiteness value ranges from 0 (pure black) to 100 (pure white). Whiteness value L ≥98 indicates that the product appears pure white visually, without any signs of yellowing, and shows good performance after 6 months in accelerated stability testing. A value of ≥97 indicates excellent color stability of the product.

[0052] Synergistic effect verification experiment: To verify the synergistic effect of two chromatographic columns in tandem, the following experiment was designed: Experimental group: Example 1 (chelating resin + anion exchange resin in series, heavy metals removed first, then chlorine removed). Control group A: Chelating resin chromatography only (Comparative example 3); Control group B: Anion exchange resin chromatography only (Comparative Example 2); Control group C: Ordinary cation exchange resin (type 732) tandem with anion exchange resin; Control group D: Anion exchange followed by chelation resin (Example 3).

[0053] The experimental results are shown in Table 2.

[0054] Table 2 shows the experimental results for verifying the synergistic effect.

[0055] The results in Table 2 are analyzed as follows: (1) The comparison results between control group A and control group B show that a single resin can only efficiently remove one type of target impurity, while the removal rate of another type of impurity is extremely low.

[0056] (2) The comparison results between the experimental group and control groups A and B showed that after the two resins were connected in series, the removal rate of their respective target impurities did not decrease and the anti-browning effect (whiteness value L after 6 months of accelerated treatment) was also improved. The effect is far superior to that of a single resin, proving that the two are synergistically linked. That is, after heavy metal ions and chloride ions are removed at the same time, the two catalytic factors of browning reaction are eliminated at the same time, and the anti-browning effect is significantly improved.

[0057] (3) The comparison results between the experimental group and the control group C show that the chelating resin (instead of ordinary cation exchange resin) selected in this invention has a significant effect. The removal rate of heavy metals by ordinary cation exchange resin is only 35.2%, which is much lower than that of chelating resin (99.2%). This is because ordinary cation exchange resin relies on electrostatic adsorption and cannot selectively capture trace heavy metal ions in the presence of a large number of sodium ions. However, chelating resin, through coordination chelation, has a selectivity for divalent heavy metal ions that is more than 5,000 times that of monovalent sodium ions. Therefore, it can efficiently remove trace heavy metals in the context of high concentration of sodium salt.

[0058] (4) The comparison results between the experimental group and the control group D showed that both process sequences could achieve good results, but the sequence of removing heavy metals first and then removing chlorine (experimental group) was better in terms of resin service life. That is, removing heavy metals first can avoid heavy metal ion contamination of subsequent anion exchange resins and extend their service life.

[0059] Resin regeneration cycle verification: The chelating resin and anion exchange resin in Example 1 were regenerated and used 20 times each. After each cycle, the removal rates of heavy metal ions and chloride ions were measured, and the results are shown in Table 3.

[0060] Table 3 shows the stability of the resin regeneration cycle.

[0061] The results in Table 3 show that after 20 regeneration-use cycles, the removal rate of both resins remained above 94%, demonstrating good regeneration stability and industrial application value.

[0062] This invention, through in-depth analysis of the browning mechanism of sodium pyruvate, identified two key impurities leading to browning—heavy metal ions (especially iron and copper ions) and chloride ions. A coupled purification scheme of chelating resin chromatography for heavy metal removal and anion exchange resin chromatography for chloride removal was specifically designed: ① Heavy metal ions (Fe³⁺) + / Fe² + Cu² +(e.g., sodium pyruvate) is a catalyst for the oxidative browning of sodium pyruvate. The iminodiacetic acid group on the chelating resin forms a stable five-membered ring chelate with heavy metal ions through the nitrogen atom and two carboxylic acid oxygen atoms. Its chelation stability is much higher than that with monovalent sodium ions. Therefore, the selectivity of the chelating resin for divalent heavy metal ions is more than 5000 times that for monovalent sodium ions. Even in high-concentration sodium pyruvate solutions, it can selectively capture trace heavy metal ions, fundamentally eliminating the active center of the catalytic oxidation reaction, which is something that ordinary cation exchange resins cannot achieve; ② Chloride ions themselves do not directly cause browning, but their presence will form chloride complexes with metal ions, enhancing the catalytic activity of metal ions. At the same time, trace amounts of oxidizing species may be formed. The quaternary ammonium group (-N) on the strongly basic anion exchange resin... + (CH3)3) undergoes an exchange reaction with chloride ions, selectively adsorbing and removing chloride ions; within a pH range of 6.5–7.5, the strongly basic resin remains fully ionized, and its chloride ion exchange capacity is unaffected by pH, with higher selectivity for chloride ions than for pyruvate ions; ③ The tandem use of two chromatographic columns produced a synergistic effect: first, heavy metal ions are removed by chelating resin, avoiding contamination of the subsequent anion exchange resin by heavy metal ions (heavy metal ions may complex with the quaternary ammonium groups of the anion exchange resin, reducing the chloride ion exchange capacity of the resin), and then chloride ions are removed by anion exchange resin, achieving optimal removal efficiency for both impurities. The results (Table 2) show that neither chromatographic column alone can simultaneously achieve chloride ≤10.0 ppm and heavy metal ≤1.0 ppm, nor can it achieve excellent anti-browning effects (whiteness value L after 6 months of accelerated processing). ≥97).

[0063] This invention addresses the problem that sodium pyruvate is prone to browning and yellowing during preparation and storage due to residual metal ions and chloride ions catalyzing oxidation. It provides a method for preparing high-purity sodium pyruvate with anti-browning properties based on ion exchange-chromatographic coupling purification. By deeply removing key impurities that cause browning, the browning reaction is inhibited at its source.

[0064] The above-described preferred embodiments of the present invention are for illustrative purposes only and are not intended to limit the scope of the invention. Any obvious variations or modifications derived from the technical solutions of the present invention are still within the protection scope of the present invention.

Claims

1. A method for preparing high-purity sodium pyruvate with anti-browning properties, characterized in that, The method includes the following steps: S1, Neutralization reaction: Pyruvic acid is dissolved in water, and then an alkaline sodium source is added to carry out a neutralization reaction to obtain sodium pyruvate neutralized solution; S2. Pre-decolorization treatment: Add activated carbon to the sodium pyruvate neutralization solution, stir and decolorize, then filter to obtain a pre-decolorized solution; S3, Heavy metal ion adsorption: The pre-decolorized solution is passed through a first chromatographic column packed with chelating resin, wherein the chelating resin is selected as an iminodiacetic acid type chelating resin or an aminophosphonic acid type chelating resin. S4. Chloride ion removal: The effluent from step S3 is passed through a second chromatographic column packed with a strong basic anion exchange resin. The functional group of the strong basic anion exchange resin is a quaternary ammonium group, which is used to selectively adsorb chloride ions in the effluent. S5. Concentration and crystallization: The effluent from step S4 is concentrated under reduced pressure, and then an antisolvent is added to crystallize, resulting in a crystalline mixture. S6. Solid-liquid separation and washing: The crystallized mixture is separated into solid and liquid phases. The obtained solid is washed with a washing solution to obtain wet sodium pyruvate. S7. Drying: The wet sodium pyruvate is dried under reduced pressure to obtain high-purity sodium pyruvate product.

2. The method for preparing high-purity sodium pyruvate with anti-browning properties according to claim 1, characterized in that, Step S1, Neutralization reaction: Pyruvic acid is dissolved in purified water, and then an alkaline sodium source is added under stirring to carry out a neutralization reaction. The reaction temperature is controlled not to exceed 40°C, and the pH of the reaction solution is adjusted to 6.5-7.5 to obtain sodium pyruvate neutralized solution. The alkaline sodium source is selected from one or more of sodium hydroxide, sodium carbonate, and sodium bicarbonate, and the molar ratio of pyruvic acid to alkaline sodium source is 1:(0.95~1.05).

3. The method for preparing high-purity sodium pyruvate with anti-browning properties according to claim 1, characterized in that, Step S2, Pre-decolorization treatment: Add activated carbon to the sodium pyruvate neutralization solution and stir at 40-60°C for 20-60 minutes to decolorize. Then filter to remove the activated carbon and obtain the pre-decolorized solution.

4. The method for preparing high-purity sodium pyruvate with anti-browning properties according to claim 1, characterized in that, In step S3, the flow rate of the pre-decolorized solution passing through the first chromatographic column is set to 2.0–5.0 BV / h; the particle size of the chelating resin is 0.3–1.2 mm; the height-to-diameter ratio of the first chromatographic column is (8–15):1; and the operating temperature is 20–30 °C.

5. The method for preparing high-purity sodium pyruvate with anti-browning properties according to claim 1, characterized in that, In step S4, the flow rate of the effluent through the second chromatographic column is set to 2.0–5.0 BV / h; the particle size of the strongly basic anion exchange resin is 0.3–1.2 mm; the height-to-diameter ratio of the second chromatographic column is (8–15):1; and the operating temperature is 20–30 °C.

6. The method for preparing high-purity sodium pyruvate with anti-browning properties according to claim 1, characterized in that, The first chromatographic column in step S3 and the second chromatographic column in step S4 are pretreated before use. The pretreatment process of the first chromatographic column is as follows: first, the first chromatographic column is regenerated by passing a 0.5-2.0 mol / L hydrochloric acid solution through it at a flow rate of 2.0-5.0 BV / h, then washed with purified water until neutral, then converted to sodium form with a 0.5-2.0 mol / L sodium hydroxide solution, and finally washed with purified water until neutral. The pretreatment process for the second chromatographic column is as follows: First, regenerate the column by passing a 0.5–2.0 mol / L sodium hydroxide solution through it at a flow rate of 2.0–5.0 BV / h, then wash with purified water until neutral, thus converting it to OH-. - type.

7. The method for preparing high-purity sodium pyruvate with anti-browning properties according to claim 1, characterized in that, Step S5, Concentration and Crystallization: The effluent is concentrated under reduced pressure in a water bath at 55-65°C and 0.05-0.1 MPa until the concentration of sodium pyruvate is 500-700 g / L. Then, the antisolvent is added dropwise and crystallized at 0-10°C for 2-6 hours to obtain a crystalline mixture. The antisolvent is anhydrous ethanol or isopropanol, the volume ratio of the antisolvent to the concentrate is (2-6):1, and the dropping rate is 1-5 ml / min.

8. The method for preparing high-purity sodium pyruvate with anti-browning properties according to claim 1, characterized in that, The washing solution in step S6 is anhydrous ethanol or an aqueous solution of ethanol with a volume fraction of 90-95%, and the washing is performed 1-3 times. In step S7, the vacuum degree of the reduced pressure drying is 0.08-0.1 MPa, the drying temperature is 50-80℃, and the drying time is 4-12 hours.

9. The method for preparing high-purity sodium pyruvate with anti-browning properties according to claim 1, characterized in that, The method further includes step S8, resin regeneration: After use, the chelating resin column of step S3 is regenerated by passing it through a 0.5–2.0 mol / L hydrochloric acid solution at a flow rate of 2.0–5.0 BV / h. The regenerated solution is collected for heavy metal recovery, and the regenerated chelating resin is recycled after being converted to the sodium form. After use, the anion exchange resin column of step S4 is regenerated by passing it through a 0.5–2.0 mol / L sodium hydroxide solution at a flow rate of 2.0–5.0 BV / h. The regenerated anion exchange resin is converted to the OH form. - It can be reused after being shaped.

10. The method for preparing high-purity sodium pyruvate with anti-browning properties according to claim 1, characterized in that, Swap the order of steps S3 and S4.